Constitutional Fragility and Dual Nationality Disputes: Legal Implications of Madagascar 2023 Presidential Election - Manitra, Ramalina Ranaivo Mikea (UIN Kiai Haji Ahmad Sidiq Jember, 2025)
The 2023 presidential election in Madagascar raised serious constitutional and legal questions surrounding the eligibility of incumbent President Andry Rajoelina, who was revealed to have acquired French nationality in 2014. This fact, under the Malagasy Code of Nationality, automatically triggers the loss of his Malagasy citizenship—an essential constitutional requirement for presidential candidacy. Despite legal provisions and widespread objections from civil society and opposition coalitions, the High Constitutional Court (HCC) dismissed all challenges and upheld his candidacy. This paper identifies a gap in existing constitutional law literature in Madagascar, which has not sufficiently addressed the legal implications of nationality loss in the context of presidential eligibility. The paper aims to examine how key legal institutions, particularly the HCC and the electoral commission (CENI), responded to this controversy and what their actions reveal about judicial independence and constitutional compliance. Using a doctrinal approach grounded in positivist and originalist lenses, complemented by judicial independence and democratic legitimacy lenses, this study analyses relevant constitutional provisions, court decisions, and political developments. It argues that the HCC’s refusal to substantively address the nationality issue reflects broader institutional weaknesses and signals a worrying trend of legal uncertainty. The findings highlight the need for reform to restore public trust, ensure electoral integrity, and safeguard constitutionalism in Madagascar.